Policy Evaluation of Village Fund Management in North Kolaka Regency - Rezky Nur Ilmi; Ismail Ismail; Sulmiah Sulmiah; Muh Nur Yamin (Universitas Negeri Makassar, 2022)
This research aims to evaluate the policy of Village Fund management activities and one of the government's strategies to help villages become self-reliant and develop the potential of the community in terms of community empowerment in managing village funds. This study adopts a qualitative research design with a descriptive approach. The subjects of this research are village officials and the community of Tojabi Village. Data collection techniques include observation, interviews, and documentation. The collected data is then processed and analyzed using the Miles, Huberman, and Saldana method, which involves data condensation, data presentation, and drawing conclusions. The research findings indicate that the community of Tojabi Village actively participates in the management of village funds through their choices of utilization and social benefits. The community's involvement takes the form of ideas, labor, and material resources.